2005
DOI: 10.1002/zaac.200500345
|View full text |Cite
|
Sign up to set email alerts
|

The Helical Coordination Polymer Ag(Nic)2(NO3)

Abstract: Single crystals of Ag(Nic)2(NO3) were obtained from an aqueous solution of silver nitrate and nicotine as plate‐like colourless crystals. The crystal structure (monoclinic, P21, Z = 2, a = 933.3(2), b = 1136.8(2), c = 1024.3(2) pm, β = 94.49(2)°) consists of helical chains in which one nicotine molecule bridges with both the pyridine‐N and the pyrrol‐N coordinating and with a second nicotine molecule terminally coordinating with the pyridine‐N. A monodentate nitrate‐O is completing the coordination sphere of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…In nicotine-copper(II) complexes,the pyrrolidine Ν atom is deprotonated. In nicotine-mercury(II) and nicotine-silver(I) compounds, the pyrrolline ring is connected through the deprotonated N2 atom to an another mercury(Π) and silver(I) atom and form a chain polymeric complexes [6,[11][12][13]. In addition, the absolut configurations of C6 and N2 can be given as S (Snicotine was used as a starting material).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In nicotine-copper(II) complexes,the pyrrolidine Ν atom is deprotonated. In nicotine-mercury(II) and nicotine-silver(I) compounds, the pyrrolline ring is connected through the deprotonated N2 atom to an another mercury(Π) and silver(I) atom and form a chain polymeric complexes [6,[11][12][13]. In addition, the absolut configurations of C6 and N2 can be given as S (Snicotine was used as a starting material).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the preparation and characterization of nicotine-metal complexes have been reported. But very little structural information on these compounds is available [4][5][6][7][8][9][10][11][12][13][14]. We have previously reported on crystal structure of the Cu(II) and Hg(ü) complexes of the type [Cu4Cu-Br)60(Nicotine) 4 ], [[HgX 2 (Nicotine)]"] (X = Br, I) [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the preparation and characterization of nicotine-metal complexes have been reported. But very little structural information on these compounds is available [4][5][6][7][8][9][10][11][12][13][14]. We have previously reported on crystal structure of the Cu(II) and Hg(II) complexes of the type [Cu 4 (m-Br) 6 O(Nicotine) 4 ], [[HgX 2 (Nicotine)] n ](X=Br, I) [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…In nicotine-copper(II) complexes,the pyrrolidine Na tom is deprotonated. In nicotine-mercury(II) and nicotine-silver(I) compounds, the pyrrolline ring is connected through the deprotonated N2 atom to an another mercury(II) and silver(I) atom and form achain polymeric complexes [6,[11][12][13]. In addition, the absolut configurations of C6 and N2 can be given as S (Snicotine was used as astarting material).…”
mentioning
confidence: 99%
“…The synthesis of such coordination polymers (CPs) is highly influenced by numerous factors such as the solvent system, temperature, counter ions with different bulk or coordination abilities, template, metal/ligand ratio and even pH [11][12]. Besides these aspects, non-covalent interactions such as hydrogen bonding, p-p interactions, and metal-metal interactions play an important role in the construction of supramolecular structures [13]. Among these polymers, the Ag(I) coordination polymers are of great interest because the Ag-donor atom bond shows the high lability and the resulting Ag(I) coordination polymers can generally be crystallized allowing investigation by X-ray diffraction [14,15].…”
Section: Introductionmentioning
confidence: 99%